(untitled) (Proceedings of Southern Federal University. Philology, 2019)
Tatyana M. Zhaplova (Orenburg, Russian Federation) The article is devoted to the study of symbolization and detailing in I.S. Turgenev’s lyrics with “manorial” motives. Referring the corpus of the poet’s lyrics, created in Russia and abroad, the author identifies the most characteristic methods of creating a poetic image of the “noble nest”, examines its specific features and functions. The analysis of the early lyricism of the so-called “Bakunin cycle” makes it possible to adjust the data related to biographical context of poems, to determine the boundaries of the archaic model of goal setting, reflected in the persona’s fate, the pathos of poems, focusing on a particular character or expressive detail of the manor. The article compares the characteristic for Turgenev ways to reflect the manorial archetype and the lyrics of its predecessors, who had founded the tradition of recreating the images of House and Garden (Park), based on the characteristics of a particular literary method, the symbolic and metaphorical images of the estate or its realistic embodiment with and easily recognizable signs – accessories of landlord life. Based on the searches of Turgenev scholars, memoirists and textologists, the author draws attention on the analysis of I.S. Turgenev’s poems, created abroad and only relatively recently included in his collected works. Autobiography and irony testify to the interest expressed by the poet in the new stages of manorial life in Russia – pre-reform and post-reform, reflected in the lyrics by realistic, natural and psychological details, succinct symbols of the noble era going into the past. Key words: symbols, detail, manor, description-lists, accessory, psychologism, landscape, portrait, elegy, message. DOI 10.23683/1995-0640-2019-3-156-163